Correlation of Penetration Rate with Drilling Parameters For an Iraqi Field Using Mud Logging Data - Hassan Abdul Hadi (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
This paper provides an attempt for modeling rate of penetration (ROP) for an Iraqi oil field with aid of mud logging data. Data of Umm Radhuma formation was selected for this modeling. These data include weight on bit, rotary speed, flow rate and mud density. A statistical approach was applied on these data for improving rate of penetration modeling. As result, an empirical linear ROP model has been developed with good fitness when compared with actual data. Also, a nonlinear regression analysis of different forms was attempted, and the results showed that the power model has good predicting capability with respect to other forms.